PENINGKATAN KEMAMPUAN TEKNOLOGI DIGITAL SISWA MELALUI APLIKASI CONSTRUCT 3: GAMES FOR EDUCATION - Afrianto, Afrianto; Wahyudin, Achmad Yudi; Surahman, Ade; Pertiwi, Fitria Azzuri Putri; Pradipta, Aurora (COMMENT: Journal of Community Empowerment, 2023)
Currently, Games for Education is an interesting topic for students in Vocational School, especially in this digital era. The training in games-making conducted by the Universitas Teknokrat Indonesia social service team gives a significant impact to develop digital competencies, creativity, and collaboration; furthermore, it is relevant to the needs of the nowadays digital job market. First, this training in this case gives the students a chance to have such a digital technology, which is relevant to the job market. It can increase their creativity in producing interesting and original digital products. Then, this training also leads the students to be able to work in a team for collaboration. In the process of game making, the students should work together to design, test, and develop the games. It thus builds up students’ ability for collaborating, communicating, and solving problems. This ability is also crucial in the digital job market, especially for project teams. Related to the job market, this training can also create a career path in game industries, graphic design, animation, and multimedia. In closing, the training gives experiences and competencies for the students in game-making that are useful for their careers; furthermore, it can help the students to master digital technology, increase their creativities, develop their collaborative ability, and to prepare themselves for the challenges of the fast- digital industry development.